Development of a moving object tracking system - Bong, Shin Feng (Universiti Malaysia Sarawak (UNIMAS), 2006)
This project presents a method for tracking moving objects in a sequence of digital images. Different methods for tracking were investigated in term of noise elimination and tracking abilities at the initial stage of the project. In this digital world and technological advancement, image processing and machine vision is becoming significant. Thus, the tracking system was developed based on the digital image processing method. This report discusses on the system background, literature, methodology, result, discussion and future system’s development. The tracking system was designed using the Matrix Laboratory (MATLAB) programming language and graphical user interface. The major features of the tracking system developed in this project are capable for tracking single and multiple objects in a static scene.